Evaluation of Infrastructure Conditions and Needs to Drive Tourism 4.0 - A.A Yenni Arini Dewi; I Wayan Runa; I Ketut Darma (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: Today, the Covid-19 pandemic has significantly impacted the tourism sector. Bali must stay alive and exist during the pandemic as a province that relies on the tourism sector. As one of the tourist attractions owned by the Province of Bali, Arts Center Cultural Park has a characteristic as a place for performances to develop artistic talents. In addition, it functions as a forum for MSMEs (Micro, Small and Medium Enterprises), especially for the Balinese people. The era of tourism 4.0 encourages the transformation of tourism objects towards digitalization. Research that examines conditions, infrastructure needs, and development strategies is needed to transform it to face the tourism era 4.0. Design/methodology/approach: This research method uses a descriptive qualitative method with interviews and literature studies. Findings: The expected results of the research are infrastructure in the form of an open stage, a performance hall, exhibition building, management building, parking, and other utilities. The digitization program that can be applied is the use of Virtual Reality (VR) and mobile technology to face the 4.0 tourism era. Paper type: Research paper